Influence of genetic characteristics of patients on systolic and diastolic function after acute myocardial infarction: a literature review - S. E. Golovenkin; S. Yu. Nikulina; M. G. Bubnova; V. N. Shulman; V. N. Maksimov (Российский кардиологический журнал, 2023)
The most important task in providing care to patients with myocardial infarction is maintaining myocardial contractility. The article discusses issues related to the influence of genetic characteristics of patients on the repair of infarcted myocardium, the remodeling process, and restoration of left ventricular systolic and diastolic function. One approach to improving the predictive ability of genetic testing is to combine information about many nucleotide sequence variants into a single risk score, often called a polygenic risk score. The article examines recent publications on the creation and use of polygenic risk scores. The use of genetic methods during examination, further consideration of the individual characteristics of each patient when choosing therapy and prescribing a course of rehabilitation will allow for an individual approach to each patient, which in turn should have a positive impact on the disease prognosis.